Aplicação de resíduo siderúrgico como adsorvente de baixo custo no tratamento de efluente têxtil - Lucena, Larissa Granjeiro (2021)
The objective of this research was to evaluate the applicability of a steelmaking waste as adsorbent in the treatment of textile effluents. First, eight types of wastes were investigated, which comprised dusts, sludge and slag coming from the diverse stages of the steelmaking process, and it was found that treating textile effluents with the Blast Furnace Sludge (BFS) reached the best results in terms of removing their organic matter (TOC) and color. Then, this process was optimized, and the following parameters were studied for the optimized reaction conditions: contact time; reaction mechanisms; performance of the proposed treatment, considering compliance with environmental legislation for textile wastewater discharge, biodegradability, metal concentration and phytotoxicity; and waste reuse and regeneration. Factorial design of Central Composite Design associated with the Response Surface Methodology were applied to optimize two operational variables: adsorbent concentration and initial reaction pH, to maximize organic matter and color removals. According to the experimental validation and the Analysis of Variance (ANOVA), all response models were statistically significant. By overlaying the contour plots, it was possible to evaluate joint interactions of pair variables on the responses and establish their optimum operational ranges: 267.09 to 341.42 g L-1 (adsorbent concentration), and 8.09 to 10.91 (pH). However, close interactions were found between these variables, and their values must be defined based on the optimal region graph to achieve removals of TOC > 80 % and color > 90 %. The time for the system to reach equilibrium, constant solute concentration in the liquid phase, was 48 hours. An increase of 2.2 % in the mass of the residue was estimated, possibly due to the mass transfer of certain components of the effluent to the waste surface. Characterization of the residue after treatment revealed no substantial changes in its chemical composition. Regarding the adsorbent-adsorbate interaction mechanisms, the computational calculations showed that the tendency is to donate electrons from the surface of the residue to the molecule of leucoíndigo blue, and that the electrostatic interaction of the dye with the positive and negative groups of the surface of the adsorbent at pH 8.5 is a probable mechanism that allows removal of that molecule from the aqueous solution. Based on UV-Vis spectrophotometry and cyclic voltammetry, the presence of reaction by-products was not identified in the treated textile effluent. The kinetic models indicated that the intraparticle diffusion is not the limiting step of the adsorption speed; and the isotherm showed a better fit to the Freundlich model. The parameters that met the discharge standards were pH, ammoniacal nitrogen, BOD5, COD, iron, copper, nickel, manganese, lead, zinc and cadmium, while fluoride and sulfate parameters did not meet the standards requiring post-treatment. It was found that the treatment employed was able to increase biodegradability and to reduce phytotoxicity of the effluent. It is possible to reuse the BFS material: 6 cycles enabled removals of 64.34 % (TOC) and 77.38 % (color). Thermal regeneration of the material, under the performed conditions, did not increase the removal of organic matter and color; however, eluents such as ethanol and acetone were applicable in the desorption process. Thus, the use of BFS as a low-cost adsorbent provided environmental benefits and proved to be an innovative and efficient technology in wastewater treatment.